First-mile walking, neighbourhood walkability and physical activity in Bangkok, Thailand - Ratanawichit, Panitat; Arifwidodo, Sigit; Anambutr, Rujiroj (Frontiers in Built Environment, 2025)
IntroductionFirst-mile walking (FMW) supports sustainable mobility and public health by enabling utilitarian and recreational walking. However, its relationship with neighbourhood walkability and physical activity remains underexplored in tropical, high-density cities like Bangkok. This study examines these associations.MethodsA cross-sectional survey of 881 Bangkok residents from 50 districts assessed neighbourhood walkability (NEWS-A) and physical activity (GPAQ). Multivariable logistic regression models examined associations between walkability, FMW, and sufficient physical activity (≥150 min/week).ResultsHigher neighbourhood walkability significantly increased both utilitarian and recreational FMW. High-rise residents were more likely to engage in utilitarian walking, while planned and high-rise neighbourhoods supported recreational walking. Utilitarian walking strongly correlated with achieving sufficient physical activity.ConclusionNeighbourhood design plays a critical role in promoting walking and physical activity. Policy efforts should prioritise pedestrian infrastructure, green spaces, and transport connectivity to encourage active lifestyles.